Makna Filosofis Kembar Mayang dalam Ritual Pernikahan Adat Jawa di Desa Kungkai Baru Kecamatan Air Periukan Kabupaten Seluma - Aini Rosidah (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2023)
Abstract: Philosophical Meanings of Mayang Twins in a Javanese Traditional Marriage Ritual in Kungkai Baru Village, Air Periukan Subdistrict, Seluma Regency. Javanese traditional wedding ceremony has a predetermined procedure. As well as one of the most important parts of Javanese traditional wedding ceremonies that is calling the bride or gathering manten. This ceremony is a ceremony when the bridegroom and bride meet, which is held at the bride's residence. This ceremony was held after the qobul consent procession was completed. In the procession of the manten gathering ceremony included various symbols that are full of meaning. One of the symbols used in this manten temon ceremony is the twin Mayang. Mayang twins are often called megar mayang or gagar mayang is one of the elements found in traditional Javanese ceremonies, in the form of flowers arranged together using fungi and leaves. Mayang twins has become a community tradition. This research uses library research method, where the authors collect data based on existing literacy. The problem formulation in this research is how is the philosophical meaning contained in the Mayang twin symbol in Kungkai Baru Village, Air Periukan Kaba District, Seluma District? The expected goal in this research is to find out the meaning of the twin mayang symbol at a traditional marriage ceremony, especially in the Kungkai Baru Village, Air Periukan Subdistrict, Seluma District, in addition, so that the community does not only know the inclusion of Mayang twins in Javanese traditional wedding ceremonies but also knows the meaning contained in symbols on the Mayang twins.